BATIK “DJAWA HOKOKAI” SEBUAH FENOMENA TENTANG BATIK DI MASA PENDUDUKAN JEPANG DI PEKALONGAN - Muh. Arif Jati Purnomo (SURYA SENI, 2009)
Batik ”Djawa Hokokai”: a Study of Batik During The Japanese Occupation in Pekalongan. Pekalongan as one of the coastal regions in Java has a strong historical root in batik paintings. The motives of the Pekalongan batik have many diferrent characteristics which differs from other batik regions that is strecthed across the northern coast of, such as Cirebon, Indramayu, Garut, and Lasem. One example of the Pekalongan Batik is the ”Djawa Hokokai” Batik, wich appeared and was developed during the Japanese occupation in 19421945.The objectives of this study are, ﬁ rst, to identify the factors which caused the emergence of the ”Djawa Hokokai” Batik, with the socio-cultural contexs which supported the development of such batik in Pekalongan. Second, to  recognized the reasons of the selection of color this was considered unsuitable for the vaguesituations and conditions at that time. Third, to acknowledge that the Japanese cultures, the coastal batik painting styles, and the royal batik painting styles have inﬂ uenced the motives and decorations which are used  in the making of ”DjawaHokokai”  Batik. The main course of study used in third reasearch was the social studies which appeared in the emergence of the ”Djawa Hokokai” Batik, and using the multidisciplinary approach.The emergence and the development of the ”Djawa Hokokai” Batik were supported by some factors. i.e the socio-cultural institutions, the  supporting societies, the batik painters, the business owners, and the brokers. In its development, the existence of the ”Djawa Hokokai” Batik is not only used as acloth for  covering the lower parts of the body (tapih) but also as an  atribute for certain habitus.The phenomenon which appeared in the ”Djawa Hokokai” Batik was basically some kinds of propagandas made  by the Japanese colonial  government to gain supports from people of Pekalongan. The term ”Djawa Hokokai” was probably one of Japanese government strategic propaganda to socialize one oftheir organizations, the ”Djawa Hokokai”.Keywords: batik Pekalongan, Djawa Hokokai, and propaganda